1999
DOI: 10.1002/(sici)1099-1379(199905)20:3<323::aid-job901>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and consequences of relational components of the new psychological contract

Abstract: SummaryThe literature regarding the new psychological contract suggests that the traditional paternalistic employer±employee relationship in U.S. companies has eroded. We investigated the relationship between relational components of the new psychological contract (personal responsibility for career development, commitment to type of work, and expectations of job insecurity), work experiences (involuntary job loss, organizational change, voluntary job change, and violation of obligations), and work outcomes (j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 0 publications
3
94
0
6
Order By: Relevance
“…The transactional determinants, including monetarist factors, are already established through communicating them before and in the early stages of the employment relationship. Relational aspects, such as loyalty and commitment to an organisation, anticipated job security or job insecurity and the disposition of a continuing relationship with an organisation, are still suggestible in this phase (Cavanaugh, 1999). Cavanaugh & Noe state that the willingness to stay in an organisation is considerably influenced by the intensity of compliance respecting relational aspects of the psychological contract.…”
Section: The Influence Of the Psychological Contract In The Employmenmentioning
confidence: 99%
“…The transactional determinants, including monetarist factors, are already established through communicating them before and in the early stages of the employment relationship. Relational aspects, such as loyalty and commitment to an organisation, anticipated job security or job insecurity and the disposition of a continuing relationship with an organisation, are still suggestible in this phase (Cavanaugh, 1999). Cavanaugh & Noe state that the willingness to stay in an organisation is considerably influenced by the intensity of compliance respecting relational aspects of the psychological contract.…”
Section: The Influence Of the Psychological Contract In The Employmenmentioning
confidence: 99%
“…In the data analysis, some variables were controlled in order to rule out alternative explanations for the findings. We controlled for age, since it has been shown that this variable can be related to psychological contract (Cavanaugh & Noe, 1999;Turnley & Feldman, 2000). Similarly to other studies (e.g.…”
Section: Fulfilment Of Agency's Obligationsmentioning
confidence: 92%
“…Transactional obligations concern specific items such as exchanges of pay and benefits that can be monetised easily. In contrast, relational obligations are comprised of socioemotional aspects that are instrumental in establishing long-term relationships but are also more nebulous (Cavanaugh and Noe, 1999). The psychological contract extends social exchange theory by examining this exchange phenomenon in an organisational setting (Morrison and Robinson, 1997;Sturges et al, 2005), and the examination of these concepts in family firms adds an additional level of complexity due to the long-standing relationships between members (Zellweger et al, 2012) and the inherent embeddedness of family-member employees within a family firm (Khanin, Turel and Mahto, 2012).…”
Section: Literature Review and Theoretical Developmentmentioning
confidence: 99%